2016
DOI: 10.1007/s12665-016-6166-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tris(2,3-dibromopropyl) isocyanurate on steroidogenesis in H295R cells

Abstract: Tris(2,3-dibromopropyl) isocyanurate (TBC) is widely used in polymer products. It is ubiquitously found in environmental matrices. Previous studies have shown that TBC has potential endocrine-disrupting effects on aquatic organisms. However, the effects on adrenocortical function and the underlying mechanisms are not well characterized. In present study, the H295R cell line was employed to investigate the potential endocrine-disrupting action of TBC. TBC inhibited basal and forskolin-induced sex hormone produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 52 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…TBC reduced the proliferation of the MCF-7 cells by 22.90% with IC 20 (concentration at 20% inhibition) and relative inhibitive potency (RIP) values of 62.20 µM and 1 × 10 –5 , respectively (Krivoshiev et al, 2016 ). The synthesis of steroid hormones takes place in gonads and suprarenal glands (Li et al, 2016 ). Forskolin is a diterpenoid capable of modulating the adenylate cyclase enzyme and cyclic adenosine monophosphate (cAMP) levels; moreover, it is also applied as a modulator of glucocorticoid and aldosterone synthesis (Purdy et al, 1991 ).…”
Section: Impact Of Tbc On Living Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…TBC reduced the proliferation of the MCF-7 cells by 22.90% with IC 20 (concentration at 20% inhibition) and relative inhibitive potency (RIP) values of 62.20 µM and 1 × 10 –5 , respectively (Krivoshiev et al, 2016 ). The synthesis of steroid hormones takes place in gonads and suprarenal glands (Li et al, 2016 ). Forskolin is a diterpenoid capable of modulating the adenylate cyclase enzyme and cyclic adenosine monophosphate (cAMP) levels; moreover, it is also applied as a modulator of glucocorticoid and aldosterone synthesis (Purdy et al, 1991 ).…”
Section: Impact Of Tbc On Living Organismsmentioning
confidence: 99%
“…Despite the lack of changes in the expression of the StAR, 3bHSD2, CYP17, CYP21, CYP19, HMGR, 17bHSD1, 17bHSD4, and CYP11A steroid genes under the influence of TBC, the use of forskolin increased the expression of the tested genes except for HMGR, 17SD1, and 17bHSD4 . In addition, the exposure of the H295R cell line to TBC induced by forskolin led to inhibition of StAR, 3bHSD2, CYP17, CYP21 , and CYP19 mRNA expression and, consequently, to inhibition of steroid hormone biosynthesis (Li et al, 2016 ). The anti-estrogenic effect of TBC was also demonstrated by inhibition of E 2 -induced proliferation of estrogen-dependent MCF7/BUS human breast cancer cells (1 nM to 10 µM TBC) and luciferase.…”
Section: Impact Of Tbc On Living Organismsmentioning
confidence: 99%
“…Nevertheless, little is known about TBC‐induced autophagy correlated with PPARγ, which is important since the mechanism of action of this dangerous xenobiotic is still unknown. Moreover, due to prove the ability of TBC to induce mitochondria‐based abnormalities in the lung cells in mouse model, however, no studies have been performed in human lung cells (Li et al, 2016). Therefore, the A549 cell line has been chosen in this work as a model of epithelium lung cells, which is justified by study shown previously (Foster et al, 1998).…”
Section: Introductionmentioning
confidence: 99%